Numerical simulation of the crack 2D by the finite element incorporated the discontinuity - Giang, Nguyen Truong (Vietnam Journal of Mechanics, 2008)
Determining stress intensity factors is important in fracture mechanics. The extended finite element method (XFEM) provides a robust and accurate to determine factors. This paper describes some results from the analysis of cracked plates using XFEM. Extended finite elements allow the entire crack to be represented independently of the meshing. The elements employ discontinuous functions and the facture mechanics two dimensional asymptotic crack tip displacement fields. The Fortran source code of Cast3M applies these elements to a set of examples. The obtained stress and deformation fields are used to compute stress intensity factors via interaction integrals. The results are compared with these obtained from conventional FEM to demonstrate the advantages of the employing the new elements.